Dr D G James FRCP and the Fellowship of Postgraduate Medicine. Issue 928 (1st February 2003) - Cook, G C
Abstract : Dr D G James recently retired as Vice President of the Fellowship of Postgraduate Medicine. The following article is based on a speech given at a dinner at the Athenaeum Club on 10 October 2002 to thank Dr James for his contributions to the Fellowship of Postgraduate Medicine over 50 years.